Fear of failure: a polynomial regression analysis of the joint impact of the perceived learning environment and personal achievement goal orientation. Issue 2 (3rd March 2020) - Giel, Lisenne I. S.; Noordzij, Gera; Noordegraaf-Eelens, Liesbeth; Denktaş, Semiha
ABSTRACT: Background and Objectives: Alongside a strong emphasis on performance and achievement in the current higher educational system, researchers have described an increase in anxiety, stress, and fear of failure amongst students. The purpose of this study was to investigate how the (mis)match between a perceived institutional performance-oriented learning environment and students' personal achievement goal orientation (mastery-approach, mastery-avoidance, performance-approach, and performance-avoidance goal orientation) related to fear or failure. Design: Cross-sectional, correlational study. Methods: Students ( N  = 329) at a highly selective college filled out questionnaires about the perceived performance-orientation in the institutional learning environment, their achievement goal orientations, and fear of failure. Results: Results of the polynomial regression analyses show that independent of each other, performance goal orientations (approach and avoidance) and the perceived institutional performance-oriented learning environment related positively to fear of failure. The results for mastery goal orientations showed that mastery-approach goal orientation attenuated, while mastery-avoidance goal orientation exacerbated the negative effects of the perceived institutional performance-oriented learning environment on fear of failure. Conclusions: These results indicate the importance of examining perceived institutional learning environments alongside students' personal characteristics in order to understand fear of failure amongst students.